A Narrative Study of Science Teaching Methods and Techniques in the New Normal - Jastine Kent Florungco; Dennis G. Caballes (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
This study aims to discover the different techniques teachers use in delivering lessons in an online class. Teachers are still adjusting to the effects of the pandemic on the education system, particularly on the delivery of learning online. It was revealed that educators tend to test various techniques in teaching the learners' competencies. Assessments play a key role in dictating the success of these methods, which is why teachers are seemed to be very cautious in conducting quizzes and exams because these may be prone to cheating since it is online nature. On the other hand, the ongoing internet issues still hound the system here in the country.